The Role of Village Apparatus in Village Financial Management Accountability (Study in Bangun Rejo Village, Tanjung Morawa District) - Assyifa Mutiara; Agus Tripriyono (International Journal of Scientific Multidisciplinary Research, 2024)
The purpose of this study was to determine the role of village officials in the financial management of Bangun Rejo Village, Tanjung Morawa District. The method used is a qualitative descriptive method. The data collection methods used are observation, interviews, and recording. These methods are then adjusted to the concept of village financial management, namely accountability and transparency. Based on the results of the research study, the accountability of Bangun Rejo Village officials in village financial management has mostly been in accordance with the applicable principles of village financial management. Although there are several obstacles, village officials have carried out their duties according to their roles. Community distrust of village leaders in managing village funds is an obstacle in Bangun Rejo Village